Bacteriological Profile and Antibiotic Susceptibility Pattern of Diabetic Foot Infection in a Tertiary Care Hospital in Lampung, Indonesia - Darwis, Iswandi; Hidayat, Hidayat; Wisnu, Gusti Ngurah P Pradnya; Mentari, Sekar (The Malaysian journal of medical sciences, 2021)
Background: Diabetic foot infection (DFI) is a serious complication of diabetes mellitus and identification of the causative bacteria is an essential step in selecting the appropriate antibiotic therapy. This study aimed to evaluate the bacterial pattern and antibiotic susceptibility of the bacteria causing DFI in Lampung Province in Indonesia. Methods: This study is a retrospective study reviewing the medical records of DFI patients admitted to the Dr Hi Abdul Moeloek Regional General Hospital in 2017–2019. DFI patients with complete medical record data were included in this study. Demographic, clinical, laboratory, wound culture and antibiotic susceptibility data were collected from the medical records using a short structural chart. The data obtained then reviewed. Results: In this study, 131 DFI patients met the study criteria and were included. Based on the wound culture results, Gram-negative bacteria were obtained in 112 (85.5%) subjects with Enterobacter spp. as the predominant bacteria. Gram-positive bacteria were found in 19 (14.5%) subjects with Staphylococcus spp. as the predominant bacteria. Gram-negative bacteria found in this study showed high susceptibility to amikacin, meropenem and sulbactam/cefoperazone. Meanwhile, the Gram-positive bacteria showed high susceptibility to meropenem, sulbactam/ cefoperazone and amikacin. Conclusion: The findings of the study revealed Enterobacter spp. as the most predominant bacteria causing DFI in the studied population. The highest antibiotic susceptibility was seen for amikacin, meropenem and sulbactam/cefoperazone.